Age at first calving: A short review of published studies in Euorpean and Zebu cattle - El-Amin, F.M. (1976)
A comparative study of age at first calving in European and zebu cattle. Various influencing factors, and their effects on other productivity parameters are described. Lack of optimum feeding and management are constraints to reducing age at first calving. There is the need to reduce this in zebu heifers.